2016
DOI: 10.1007/s10286-016-0349-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the safety and efficacy of droxidopa for neurogenic orthostatic hypotension

Abstract: Droxidopa is a safe and effective drug for the short-term management of NOH symptoms. However, current evidence is insufficient to confirm the efficacy of droxidopa for long-term use. Therefore, further studies with increased sample size are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Starting this patient on droxidopa, which is a synthetic precursor of NE [1, 4], is a reasonable option at this stage. Additionally, given that this patient needs to nap several times daily, there is a mechanistic hypothesis that increasing NE levels in the CNS may potentially improve other non-motor symptoms in PD [2], although no large studies have been performed to confirm this.…”
Section: Expert Commentary (Dr Claassen)mentioning
confidence: 99%
“…Starting this patient on droxidopa, which is a synthetic precursor of NE [1, 4], is a reasonable option at this stage. Additionally, given that this patient needs to nap several times daily, there is a mechanistic hypothesis that increasing NE levels in the CNS may potentially improve other non-motor symptoms in PD [2], although no large studies have been performed to confirm this.…”
Section: Expert Commentary (Dr Claassen)mentioning
confidence: 99%
“…At that time, orthostatic blood pressure (BP) readings confirmed that she was experiencing a large fall in BP (170/87 mmHg supine to 110/65 mmHg after 3-min of standing-up) while her heart rate (HR) increased by only 10 beats per minute or less; therefore, she was diagnosed with neurogenic orthostatic hypotension (nOH). Droxidopa was initiated at 100 mg on a modified three times daily (TID) schedule (taken on awakening, at midday, and at least 3–4 h prior to bedtime) [1, 3]. Her droxidopa dose was up-titrated every 24–48 h by 100 mg on the modified TID schedule.…”
Section: Case Presentationmentioning
confidence: 99%
“…Droxidopa is FDA-approved for the treatment of symptomatic nOH in PD and has demonstrated favorable tolerability [2, 3]. A potential side effect of droxidopa is sHTN.…”
Section: Expert Commentary (Dr Kremens)mentioning
confidence: 99%